Exploring the effects of a cervical strengthening program on purposeful soccer heading biomechanics - Waring, K.; Bowman, T.; Austin, G.; Smith, E. (The Journal of Strength and Conditioning Research, 2021)
Context: Cervical neck strengthening has been proposed as an important factor in concussion prevention. However, the effect of cervical neck strengthening programs on purposeful heading biomechanics has not been identified. The purpose of our study was to determine if a 6-week strengthening program changed purposeful heading biomechanics. Methods: 20 collegiate soccer athletes (8 males, 12 females, age = 20.15 ± 1.35 years, height = 171.67 ± 9.01 cm, mass = 70.56 ± 11.03 kg) volunteered to participate. Time (pre, post) and group (experimental, control) served as the independent variables. Heading biomechanics from xPatch sensors (peak linear acceleration (PLA), peak rotational acceleration (PRA), and duration) served as the dependent variables. Each subject wore an xPatch sensor to gather heading biomechanics data while heading 10 soccer balls at 2 speeds (40 and 64 km/h). The experimental group completed specific cervical neck strengthening exercises twice a week for 6 weeks using a Shingo Imara cervical neck resistance apparatus. The exercises consisted of 2 sets of 4 cervical neck movements until fatigue. The control group did not perform cervical neck strengthening exercises. After 6 weeks, the subjects completed the same heading protocol. We analyzed the data using 2 × 2 mixed model ANOVAs for each dependent variable. Results: There was no interaction present between group and time for PLA at 40 km/h (F1,11 = 0.66, p = 0.43, Eta² = 0.06) or 64 km/h (F1,11 = 0.98, p = 0.34, Eta² = 0.08). There was also no interaction present between group and time for PRA at 40 km/h (F1,11 < 0.01, p = 0.96, Eta² < 0.001) or 64 km/h (F1,11 < 0.01, p = 0.97, Eta² = 0.0). Finally, there was no interaction present between group and time for duration at 40 km/h (F1,11 = 0.41, p = 0.53, Eta² = 0.04) or 64 km/h (F1,11 = 0.08, p = 0.79, Eta² < 0.01). Conclusions: The cervical neck strengthening protocol did not affect heading biomechanics. The link between cervical neck strengthening and concussion predisposition should continue to be explored.